Inhibitory B cell co-receptors and autoimmune diseases. Issue 3 (3rd July 2019) - Tsubata, Takeshi
Abstract: B cells express various inhibitory co-receptors including CD22 (also known as Siglec-2), Siglec-10 (Siglec-G in mice), CD72, LILRB (PIR-B in mice) and FcγRIIB that contain immunoreceptor tyrosine-based inhibition motifs (ITIMs) in the cytoplasmic region and negatively regulate BCR signaling by recruiting phosphatases to the ITIMs. Some of the inhibitory B cell co-receptors suppress development of SLE. Among these, CD72 most strongly regulates SLE. CD72 recognizes Sm/RNP, a lupus self-antigen and an endogenous TLR7 ligand, as a specific ligand, and suppresses B cell response to this TLR7 ligand. This suppression may inhibit development of SLE because TLR7 is indispensable in multiple mouse SLE models. In contrast, inhibitory B cell co-receptors such as CD22 and CD72 inhibit expansion of regulatory B cells that are known to regulate development of autoimmune diseases including type 1 diabetes (T1D) and multiple sclerosis. CD72 strongly exacerbate development of T1D in NOD mice probably by limiting expansion of regulatory B cells. Thus, inhibitory B cell co-receptors especially CD72 regulates distinct autoimmune diseases either positively or negatively. As B cell depletion therapy clearly reveals crucial roles of B cells in the regulation of various autoimmune diseases, CD72 may be a novel therapeutic target for treatment of autoimmune diseases.